Systemic Lupus Erythematosus Associated Pitfalls on (18)F-FDG PET/CT: Reactive Follicular Hyperplasia, Kikuchi-Fujimoto Disease, Inflammation and Lymphoid Hyperplasia of the Spleen Mimicking Lymphoma - Makis, William (Nucl Med Mol Imaging, 2017)
Systemic lupus erythematosus (SLE) is associated with a variety of inflammatory processes that can affect the lymph nodes, brain, kidneys, and spleen. We present two patients with SLE in whom SLE-associated conditions complicated interpretation of (18)F-fluoro-2-deoxy-d-glucose ((18)F-FDG) positron emission tomography/computed tomography (PET/CT) imaging of the lymph nodes and the spleen. The imaging findings mimicked lymphoma, but histopathological evaluation showed benign processes including reactive follicular hyperplasia in the lymph nodes, Kikuchi-Fujimoto disease in perisplenic lymph nodes, and inflammatory changes and lymphoid hyperplasia in the spleen.